Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let's solve each of the equations step-by-step:
### Part a) Solve [tex]\(2(x+3) = x-4\)[/tex]
1. Expand the left side:
[tex]\[ 2(x+3) = 2x + 6 \][/tex]
So the equation becomes:
[tex]\[ 2x + 6 = x - 4 \][/tex]
2. Move all terms involving [tex]\(x\)[/tex] to one side by subtracting [tex]\(x\)[/tex] from both sides:
[tex]\[ 2x + 6 - x = x - 4 - x \][/tex]
Simplifying this gives:
[tex]\[ x + 6 = -4 \][/tex]
3. Isolate [tex]\(x\)[/tex] by subtracting 6 from both sides:
[tex]\[ x + 6 - 6 = -4 - 6 \][/tex]
Simplifying this gives:
[tex]\[ x = -10 \][/tex]
So the solution to part a) is:
[tex]\[ x = -10 \][/tex]
### Part b) Solve [tex]\(4(5x - 2) = 2(9x + 3)\)[/tex]
1. Expand both sides:
[tex]\[ 4(5x - 2) = 20x - 8 \][/tex]
[tex]\[ 2(9x + 3) = 18x + 6 \][/tex]
So the equation becomes:
[tex]\[ 20x - 8 = 18x + 6 \][/tex]
2. Move all terms involving [tex]\(x\)[/tex] to one side by subtracting [tex]\(18x\)[/tex] from both sides:
[tex]\[ 20x - 18x - 8 = 18x - 18x + 6 \][/tex]
Simplifying this gives:
[tex]\[ 2x - 8 = 6 \][/tex]
3. Isolate [tex]\(x\)[/tex] by adding 8 to both sides:
[tex]\[ 2x - 8 + 8 = 6 + 8 \][/tex]
Simplifying this gives:
[tex]\[ 2x = 14 \][/tex]
4. Solve for [tex]\(x\)[/tex] by dividing both sides by 2:
[tex]\[ x = \frac{14}{2} \][/tex]
Simplifying this gives:
[tex]\[ x = 7 \][/tex]
So the solution to part b) is:
[tex]\[ x = 7 \][/tex]
In summary:
- For part a), [tex]\(x = -10\)[/tex]
- For part b), [tex]\(x = 7\)[/tex]
### Part a) Solve [tex]\(2(x+3) = x-4\)[/tex]
1. Expand the left side:
[tex]\[ 2(x+3) = 2x + 6 \][/tex]
So the equation becomes:
[tex]\[ 2x + 6 = x - 4 \][/tex]
2. Move all terms involving [tex]\(x\)[/tex] to one side by subtracting [tex]\(x\)[/tex] from both sides:
[tex]\[ 2x + 6 - x = x - 4 - x \][/tex]
Simplifying this gives:
[tex]\[ x + 6 = -4 \][/tex]
3. Isolate [tex]\(x\)[/tex] by subtracting 6 from both sides:
[tex]\[ x + 6 - 6 = -4 - 6 \][/tex]
Simplifying this gives:
[tex]\[ x = -10 \][/tex]
So the solution to part a) is:
[tex]\[ x = -10 \][/tex]
### Part b) Solve [tex]\(4(5x - 2) = 2(9x + 3)\)[/tex]
1. Expand both sides:
[tex]\[ 4(5x - 2) = 20x - 8 \][/tex]
[tex]\[ 2(9x + 3) = 18x + 6 \][/tex]
So the equation becomes:
[tex]\[ 20x - 8 = 18x + 6 \][/tex]
2. Move all terms involving [tex]\(x\)[/tex] to one side by subtracting [tex]\(18x\)[/tex] from both sides:
[tex]\[ 20x - 18x - 8 = 18x - 18x + 6 \][/tex]
Simplifying this gives:
[tex]\[ 2x - 8 = 6 \][/tex]
3. Isolate [tex]\(x\)[/tex] by adding 8 to both sides:
[tex]\[ 2x - 8 + 8 = 6 + 8 \][/tex]
Simplifying this gives:
[tex]\[ 2x = 14 \][/tex]
4. Solve for [tex]\(x\)[/tex] by dividing both sides by 2:
[tex]\[ x = \frac{14}{2} \][/tex]
Simplifying this gives:
[tex]\[ x = 7 \][/tex]
So the solution to part b) is:
[tex]\[ x = 7 \][/tex]
In summary:
- For part a), [tex]\(x = -10\)[/tex]
- For part b), [tex]\(x = 7\)[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.